An Evaluation Study of the Academic Performance of a Faculty Member in the College of Education from the Point of View of Graduate Students (Damascus University Journal of educational and Psychologyical sciences, 2022)
The current research aims to define the degree of evaluating the academic performance of a faculty member in the College of Education from the point of view of graduate students, and to identify the differences in assessing the reality of academic performance according to the student’s gender and academic level (MA - PhD).The research used the descriptive and analytical method and one of its tools represented by the questionnaire that was applied to a sample of (213) graduate students (MA - PhD) in the Faculty of Education at the University of Damascus.The research reached several results, the most important of which are:The personal behaviors of the faculty member came with a high degree in academic performance.The academic faculty member’s performance in the field of scientific empowerment, scientific research and community service was moderate.- The absence of statistically significant differences between the averages of the respondents’ answers about the reality of the academic performance of the faculty member in the College of Education at the macro level and at the level of all axes (practical mastery - scientific research - community service - personal behaviors) according to the gender variable.- There are no statistically significant differences between the averages of the respondents’ answers about the reality of the academic performance of the faculty member in the College of Education at the macro level and at the level of all axes (practical mastery - scientific research - community service - personal behaviors) according to the academic level variable (Master - PhD).
Keywords: academic performance; faculty member.